Pengaruh Efektivitas Self Assessment System terhadap Penerimaan Pajak Pertambahan Nilai (PPN) pada Kantor Pelayanan Pajak Pratama Kendari - Daud, Laode Turisno (JURNAL AKUNTANSI, 2016)
This study aims to determine the effectiveness of the Self Assessment System Effect on acceptance of Value Added Tax (VAT) on the Tax Office Service Kendari.The data used in this study is quantitative data and qualitative data, the data source used is primary data that is the source of data obtained directly from the taxpayer that is in the Southeast, especially in Kendari and secondary data is already available VAT from the Tax Office Service Kendari documentation. The data obtained were processed using simple linear regression analysis is to look for how much influence the effectiveness of the Self Assessment System on acceptance of Value Added Tax (VAT) on the Tax Office Service Kendari.The results showed that the effectiveness of the Self Assessment System has a significant influence on the acceptance of Value Added Tax (VAT) on the Tax Office Service Kendari. Contributions variables Effectiveness Self Assessment System on acceptance of Value Added Tax (VAT) 0.323 or 32.3%, while the remaining 67.7% is the influence of other variables in the model are not included in this study. Internal control system variables obtained t-count of 4,260 is greater than t-table value of 1.684 with a t-sig at 0.010. obtained t-sig smaller than a=0,05 so the null hypothesis is rejected, which means Effectiveness Self Assessment System has a significant influence on the acceptance of Value Added Tax. That is, if the Self Assessment System Effectiveness run properly can increase the acceptance of Value Added Tax.Â Keywords: Effectiveness Self Assessment System, Value Added Tax.